Effect of educational intervention on intern physician’s knowledge and attitude towards pharmacovigilance in selected tertiary hospitals of Bangladesh: Educational intervention and pharmacovigilance - Shamsuddoha, Nazla; Rahman, Md Sayedur; Ferdous, Asiya; Islam, Sultana Aktia; Rahman, Saba Md Rezwanur; Ahmad, Rahnuma; Parvin, Roksana; Sultana, Nusrat (Journal of the Medical College for Women & Hospital, 2024)
Background: Adverse Drug Events (ADEs) are a major public health issue linked to poor treatment outcomes, increased morbidity and mortality, and significant economic burdens. Pharmacovigilance, essential for detecting and preventing adverse medication effects, addresses these concerns. While initial pharmaceutical evaluations reveal only half of the potential hazards, post-marketing surveillance identifies the rest, highlighting the need for effective pharmacovigilance. However, Bangladesh lacks a robust system. Aim: This study aimed to evaluate the impact of educational interventions on intern physicians' knowledge and attitudes towards pharmacovigilance. Materials and Method: This formative interventional research was conducted among intern physicians at Dhaka Medical College Hospital, Ad-din Women’s Medical College Hospital, Medical College for Women and Hospital, and Anwer Khan Modern Medical College Hospital. A total of 208 interns were recruited, with 189 completing the structured questionnaire survey. These respondents were divided into two groups: a control group (n=89) and an intervention group (n=100). Baseline and post-intervention data on knowledge, awareness, attitude, and experiences were collected via the questionnaire. The intervention group received a package of educational interventions, including workshops, focus group discussions, and key informant interviews, along with a suspected adverse event reporting form. Data analysis was conducted using an online statistical analytic calculator and Microsoft Office Excel. Results: At baseline, there were no statistically significant differences in knowledge and attitudes between the control and intervention groups. However, post-intervention, the knowledge and attitudes regarding pharmacovigilance significantly improved among the intervention group. Specifically, the knowledge of ADE reporting importance was 53.9% in the control group and 95% in the intervention group; the procedure for ADE detection and reporting was 19.1% and 91%, in the control and intervention group respectively; awareness of the yellow card system rose to 92% in the intervention group; knowledge of the location of the International Center of ADR (Adverse Drug Reaction) Monitoring was 22.5% in the control group and 89% in the intervention group; awareness of the national pharmacovigilance program was 30.3% (control) and 85% (intervention); and understanding of the responsible regulatory body in Bangladesh went up from 52% to 86% from baseline to after intervention. These improvements were statistically significant. Additionally, attitudes towards the necessity of ADE reporting were more positive in the intervention group, with 94% recognizing its importance compared to 78.7% in the control group. Furthermore, 91% of the intervention group considered ADE reporting a professional obligation, versus 67.4% in the control group, and 96% of the intervention group had received pharmacovigilance training. Conclusion: The educational intervention effectively improved the knowledge and attitudes of intern physicians regarding pharmacovigilance. J Med Coll Women Hosp. 2024; 20(1): 50-59